What is a Black Hole? - Orlov, S. (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2016)
A new physical model of an astronomical object - Black Hole. Presented by the equation for determining the radius of the object, based on the theory of vortex gravitation. Proposed rationale that the black hole mass does not depend on the strength of gravity on its surface. Schwarzschild solution shows a contradiction by definition radius of the Black Hole.